Fear-focused Self-compassion Therapy for young breast cancer patients' fear of cancer recurrence: Study protocol of a randomized controlled trial - Wei, Liuyu; Yang, Xiaomin; Sun, Shasha; Yu, Yunlei; Xie, Juan; Zhao, Jiang; Wang, Xiao; Zhu, Lei; Yao, Juntao (Frontiers in Psychiatry, 2022)
Background In China, there are a growing number of young women being diagnosed with breast cancer. Fear of Cancer Recurrence (FCR) has become one of the major psychological concerns reported by young breast cancer patients. Yet, there is a lack of psychological intervention tailored for reducing FCR for Chinese young breast cancer patients. In the current study, the Fear-focused Self-compassion Therapy is developed to help Chinese young breast cancer patients to manage FCR. The therapy was developed based on FCR development theories and self-compassion related therapy. The primary objective is to evaluate the short-term and long-term effectiveness of Fear-focused Self-compassion Therapy. The secondary objective is to examine the underlying mechanisms of therapy in reducing FCR in young breast cancer patients. Methods The Fear-focused Self-compassion Therapy consists of 8-week face to face group sessions. This study will be a randomized controlled trial with 160 Chinese young female breast cancer patients with severe FCR. Participants will be randomized to the therapy group or a usual care control group (1:1). Measurements will be completed at baseline, immediately completing intervention, 3, 6, and 12 months later. Primary outcomes are FCR severity, and secondary outcomes include symptoms of depression and anxiety, satisfaction with therapy, and cost-effectiveness of the therapy. Discussion If successful, this study will provide an effective psychological intervention to treat FCR for young breast cancer patients in China, and illuminate the underlying mechanisms of the Fear-focused Self-compassion Therapy in reducing FCR. Clinical trial registration ClinicalTrials.gov: NCT04965428. Registered 23rd July 2021, https://clinicaltrials.gov/ct2/show/NCT04965428?cond=fear+of+cancer+recurrence&draw=2&rank=1